2004
DOI: 10.1111/j.0022-202x.2004.23458.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Interacts with Transforming Growth Factor-β Signaling to Mediate Keratinocyte Growth Arrest and Chemotaxis

Abstract: Lysophosphatidic acid (LPA, 1-acyl-glycerol-3-phosphate) plays an important role in diverse biological responses including cell proliferation, differentiation, survival, migration, and tumor cell invasion. The most prominent source of LPA is platelets from which it is released after thrombin activation and is assumed to be an essential function of this lysophospholipid in cutaneous wound closure. Therefore, we examined the role of LPA on biological responses of keratinocytes. Although LPA potently enhances ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
5
21
0
Order By: Relevance
“…There might be some mechanistic link between cell cycle arrest and migration/invasion of tumor cells. For example, metastasis of tumor cell induced by cytokines such as transforming growth factor-h is often accompanied by growth inhibition (38,39). Interestingly, a lot of studies showed that PKC might crosstalk with or even mediate the effect of transforming growth factor-h signaling (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…There might be some mechanistic link between cell cycle arrest and migration/invasion of tumor cells. For example, metastasis of tumor cell induced by cytokines such as transforming growth factor-h is often accompanied by growth inhibition (38,39). Interestingly, a lot of studies showed that PKC might crosstalk with or even mediate the effect of transforming growth factor-h signaling (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Sauer et al (2004) showed that LPA mediates keratinocyte growth arrest and chemotaxis. The effects of LPA on wound healing have also been studied in intestinal epithelial cells (Liliom et al, 1998;Sturm et al, 1998;Hines et al, 2000), where LPA induced migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-receptor binding in the LPA/LPA1 signaling pathway promotes migration and enhances wound healing in vivo [7, 8]. In current study, we investigated the effect of TrkA on LPA-induced cell migration in lung epithelial cells and found that TrkA tyrosine kinase inhibitor or reduction of TrkA level significantly attenuated the LPA-induced cell migration.…”
Section: Discussionmentioning
confidence: 95%
“…LPA is a crucial mediator of physiological processes including cell proliferation, survival, migration, differentiation, adhesion and morphology, as well as pathological processes in cancer, fibrosis, bone metabolism and reproduction [3, 4]. In the setting of wound repair, LPA is released from serum by a platelet-dependent pathway [1] at the site of acute injury [5, 6], and then LPA promotes cell migration [7] and thus enhances wound healing [8]. …”
Section: Introductionmentioning
confidence: 99%